Dekonstruksi Dikotomi Menggagas Spiritualisasi Human Being dalam Pendidikan Islam - Bahar Agus Setiawan (Universitas Muhammadiyah Jember, 2019)
Education as a conscious and planned effort as stated in the National Education System Act no. 20, 2003 relates to three developmental targets, namely: the development of spiritual power, intelligence and morality. However, the existence of dichotomy in science and education makes the direction of education lose its essential weight. For this reason, such a dichotomy must be deconstructed to produce synergy and integration between intellectual and spiritual entity. Education in general and Islamic education in particular must not be conceived partially, so the core value of education can be realized. The idea of human as a living spiritual entity in Islamic education can be realized by revitalizing and conceptualizing the role and meaning of Islamic education by developing and changing curriculum in both content and purpose, as an effort to entrench spirituality as the basis of orienting Islamic education.